Psilochilus dressleri (Orchidaceae), a new species from the Darién Gap, Panama - Kolanowska, Marta (Phytotaxa, 2014)
A new species, Psilochilus dressleri, is described and illustrated. It resembles P. macrophyllus, but both species differ in the lip form.